2014
DOI: 10.1007/s40089-014-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology effects of nickel nanoparticles on lungs, liver, and spleen tissues in male mice

Abstract: Because of the classification of the nickel compounds as carcinogenic substances, there is a need for in vivo tests to nickel nanoparticles (NiNPs) for observing their effects on health experimentally. Spherical NiNPs with 10 nm in diameter and 75 ppm concentration were applied for investigating their toxicities within male albino mice as an in vivo model. We randomly made sham group, control group, and 75 ppm group (with five animals in each group). Then, the nanoparticles were injected into mice intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…After intravesical instillation chemotherapy, the PTX/CS blends, and PTX/CS NSs showed prolonged survival and the survival rate of PTX/CS NSs was the highest (Figure B). Many researchers have reported that the nanomaterials tend to accumulate in liver and kidney because the liver and kidney are the main detoxifying organs. Therefore, it is very important to examine the influence of PTX/CS NSs on liver and kidney function. The blood clinical chemistry level measuring is a simple and reliable indication of kidney and liver health.…”
Section: Resultsmentioning
confidence: 99%
“…After intravesical instillation chemotherapy, the PTX/CS blends, and PTX/CS NSs showed prolonged survival and the survival rate of PTX/CS NSs was the highest (Figure B). Many researchers have reported that the nanomaterials tend to accumulate in liver and kidney because the liver and kidney are the main detoxifying organs. Therefore, it is very important to examine the influence of PTX/CS NSs on liver and kidney function. The blood clinical chemistry level measuring is a simple and reliable indication of kidney and liver health.…”
Section: Resultsmentioning
confidence: 99%
“…The histopathological analysis marked liver congestion, steatosis, zonal necrosis, and inflammatory cell infiltration in portal vein areas after Ni NP exposure. The increased bilirubin may lead to hyperbilirubinemia and cholestasis that is coupled with an increased level of ALP and AST that induces liver necrosis at zonal areas owing to obstruction of bile ducts and infiltration of excessive bile in the portal and central vein that leads to necrosis (Magaye et al, 2014; Alarifi et al, 2013; Ajdari and Marziyeh, 2014). The nanoparticles are entered into the blood and reach the target organs where NPs induce necrosis owing to changes in various biochemical biomarkers that increase the cellular pressure because of electrolyte imbalance and cause dose-dependent abnormalities in histoarchitecture (Nel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ajdari, and M.Z. Ghahnavieh, [14] have investigate the histopathology effects of Nickel Nano-particles (NiNPs) on the lungs, liver and spleen tissues in male mice. The histopathologic investigation result showed that the low to high abnormalities in the liver, spleen, and lung tissues were treated in mice by employing Ni-NPs.…”
Section: Literature Reviewmentioning
confidence: 99%